A new natural hybrid in Argemone (Papaveraceae) - Otto, Rainer; Verloove, Filip (Phytotaxa, 2016)
Argemone × hybrida is described as a natural hybrid of A. mexicana and A. ochroleuca, based on a collection from La Palma (Canary Islands, Spain), where both parents are found growing in close proximity. This hybrid may be more widespread but overlooked. Distinguishing features of all three taxa are thoroughly discussed and illustrated.